Effects of impact energy on the wear resistance and work hardening mechanism of medium manganese austenitic steel - Hui Chen; Dong Zhao; Qingliang Wang; Yinghuai Qiang; Jianwei Qi (Friction)
Abstract Medium manganese austenitic steel (MMAS) fabricated through the hot rolling process has been used in the mining, military, and mechanical industries. In this paper, the abrasion performance and hardening mechanism were measured under a series of impact energies. The impact wear was tested at different impact energies from 0.5 J to 6 J using a dynamic load abrasive wear tester (MLD-10). Microstructure and surface morphologies were analyzed using scanning electron microscopy, X-Ray diffraction, and transmission electron microscopy. The results suggest that MMSA has the best wear resistance at 3.5 J and the worst wear resistance at 1.5 J. Furthermore, the wear mechanism and worn surface microstructure change with different impact energies. There are small differences between a large amount of martensite on the worn surfaces under different impact energies and the shapes of dislocation and twins change with different impact energies.